Adsorption of Cd (II) into Activated Charcoal from Matoa Fruit Peel - Kustomo Kustomo; Naila Lajja Zulfa Faza; Andreas Haarstrick (Department of Chemistry Faculty of Science and Technology Walisongo, 2022)
Cadmium (Cd) is one of the heavy metals with a high level of contaminants that is environmentally harmful and can interfere with human health. This study aims to determine the adsorption capacity and adsorption kinetics of Cd (II) from Matoa fruit peel activated by nitric acid. The adsorption method can be used to treat Cd (II) waste in the water. Activated charcoal is used for adsorption. The charcoal produces a relatively 1.17 % ash content, 3.92 % water content, and a 507.64 mg/g iodine absorption test. Based on the results of FTIR characterization, it is known that the O-H and C=O groups play an important role in adsorption. The SEM-EDX characterization produced a carbon content of 99.21 %. At pH 9, activated charcoal adsorbs Cd (II) metal effectively, with a contact time of 40 minutes and a concentration of 20 ppm. The activated charcoal of Matoa fruit peel activated by nitric acid had an adsorption capacity of 59.75 mg/g. It used a pseudo-second-order reaction for the chemical kinetics equation and the Langmuir adsorption isotherm equation for the adsorption isotherm.